1998
DOI: 10.1080/001401398186559
|View full text |Cite
|
Sign up to set email alerts
|

In search of better route guidance instructions

Abstract: Safety concerns have prompted designers of in-vehicle route guidance and information systems (IVRGIS) to make more use of an 'audible interface' to convey guidance instructions. Previous research has shown that, contrary to expectations, detailed guidance instructions can have a detrimental effect upon wayfinding performance, particularly for elderly individuals. In response to these findings a second series of experiments was carried out to try to improve the effectiveness of route guidance. Using the same pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
0
17
1
1
Order By: Relevance
“…A range of studies has empirically demonstrated how landmarks have the potential to enhance driver navigation systems in terms of: (1) effective navigation decisions (Tom & Denis, 2003;Jackson, 1998;Bengler, Haller, & Zimmer, 1994); (2) reduced cognitive effort and distraction (Burnett, 1998), and (3) increased confidence and satisfaction (Alm, Nilsson, Jarmark, Savelid, & Hennings, 1992;Green, Hoekstra, Williams, Wen, & George, 1993). However, little, if any, research has been published that assesses the extent to which driver performance, within a real navigation context, is affected by the quality of the landmark, i.e.…”
Section: The Practical Benefits Of Landmarks For Driver Navigationmentioning
confidence: 99%
“…A range of studies has empirically demonstrated how landmarks have the potential to enhance driver navigation systems in terms of: (1) effective navigation decisions (Tom & Denis, 2003;Jackson, 1998;Bengler, Haller, & Zimmer, 1994); (2) reduced cognitive effort and distraction (Burnett, 1998), and (3) increased confidence and satisfaction (Alm, Nilsson, Jarmark, Savelid, & Hennings, 1992;Green, Hoekstra, Williams, Wen, & George, 1993). However, little, if any, research has been published that assesses the extent to which driver performance, within a real navigation context, is affected by the quality of the landmark, i.e.…”
Section: The Practical Benefits Of Landmarks For Driver Navigationmentioning
confidence: 99%
“…When people recall route information, they decompose the route into a set of discrete route parts, consisting of only minimal information such as turns and landmarks at the turns, in congruence with effective wayfinding aids (Jackson, 1998). The turns in route directions are key decision points in which the user has to remember to re-orient himself in order to remain on the route.…”
Section: Dynamic Vs Static Presentation Of Route Informationmentioning
confidence: 99%
“…A range of studies has empirically demonstrated how landmarks have the potential to enhance driver navigation systems in terms of: (1) effective navigation decisions (Tom & Denis, 2003); (Jackson, 1998); (Bengler, Haller, & Zimmer, 1994); (2) reduced cognitive effort and distraction (Burnett, 1998), and (3) increased confidence and satisfaction (Alm, Nilsson, Jarmark, Savelid, & Hennings, 1992;Green, Hoekstra, Williams, Wen, & George, 1993). (Dingus et al, 1997) has shown that although older drivers had difficulty driving and navigating simultaneously, and made more safety-related errors than younger drivers, they also benefited considerably from a well designed HMI.…”
Section: Modalitiesmentioning
confidence: 99%